Головні віхи історії археозоологічних досліджень в Україні - Ступак, А.В.; Горбаненко, С.А. (Археологія і давня історія України, 2022)
У статті здійснено огляд розвитку археозоології в Україні. Ця галузь знань має понад столітню
історію й пройшла шлях від окремого напряму в
зоології до окремої наукової дисципліни станом
натепер. Зазначений внесок в її розвиток окремих
персоналій, а також інституцій, які ставали центрами археозоологічних досліджень в різні часи. The primary focus of this research is the history of
archaeozoological studies in Ukraine. Like every scientific
branch, the development of archaeozoology has
the stages of its beginning, generation, and separation
of individual scientific discipline. The rise of scientific
interest in the evolutionary process and fossil fauna at
the end of the 19th century promote the investigation
of the faunal remains of the relative modern geological
period — Quaternary. The large number of ungulates
faunal remains of this period was found on archaeological
sites.
Olexandr Brauner, was the first zoologist who
worked with the faunal remains from archeological
sites of Kherson region. As an archaeozoologist, V. Gromova
actively participated in the research of faunal
collections from the different archaeological sites of
Ukraine. She compiled the almost first atlases of mammals
anatomy for archaeozoologists.
Ivan Pidoplichko is the founder of the archaeozoological
school in Ukraine. His professional career began
from organization of the working group of archaeozoologists
to the head of the Paleozoological department
of the Institute of Zoology of Academy of Sciences of
UkrSSR (now Schmalhausen Institute of Zoology).
Ivan Pidoplichko also is the founder of the National
Museum of Natural history which is one of the centers
of archaeozoological studies. Well known archaeozoologists
such as V. Bibikva, N. Bilan (Tymchenko), N. Kornijetz,
V. Topachevski, P. Puchkov, and O. Zhuravliov
worked under the lead of Ivan Pidoplichko. In the
1970s O. Zhuravliov started to work in the Institute
of Archaeology Academy of Sciences of the UkrSSR.
During the last two decadesYe. Yanish, M. Kublij,
T. Bitkovska, A. Stupak and O. Seniuk joined archaeozoological
studies. The current archaeozoology studies
in Ukraine are still developing.